(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Justicia gendarussa Burm. f (J. gendarussa) is a flora part of Acanthaceae family, is a herbal remedy localized to numerous regions of Asia, which has been used since ancient times for its traditionally claimed pharmacological activities. J. gendarussa is a fast-developing bush that discovered in the tropical shady and moist places. Mostly this plant is found in China, hence also known as Chinese medicinal plant. Over the past few years, it has gathered significant attention due to its diverse pharmacological activities and rich chemical composition. Pharmacological investigations have revealed that J. gendarussa possesses a broad spectrum of biological activities, comprising, although not restricted to anti-HIV, anti-inflammatory, analgesic, anxiolytic, anti-microbial, hepatoprotective, anti-fungal, antioxidant, larvicidal, anthelmintic and antiarthritic. Furthermore, chemical analyses of J. gendarussa have identified a wide array of bioactive constituents, like alkaloids, flavonoids, terpenoids, phenols, carbohydrates and fatty acids. These phytochemicals play pivotal roles in mediating the observed pharmacological activities and hold promise for the creation of novel medications or supplements targeting the various health conditions. This review focuses on the pharmacological profile, bioactive components, and ethanobotanical significance of J. gendarussa. This inclusive assessment provides an extensive study of the current state of research on J. gendarussa, encompassing its pharmacological effects and chemical constituents. By consolidating existing knowledge, scholars and practitioners alike can benefit greatly from this review, fostering advanced exploration of this remarkable plant species for therapeutic purpose.